A cidade verde, imagens e discursos: o caso de Maringá (PR) Brasil - Bovo, Marcos Clair; De Costa Trindade Amorim, Margarete Cristiane (My University, 2012)
This research aims at presenting a brief reflection concerning the cidade verde image that predominates in the city of Maringá-PR, highlighting the conception of garden-city, the images and discourses that convey in the media, followed by the main proposals implanted in the city referring to environmental law. Thus we try to investigate the action of the marketing speech Maringá Cidade Verde through advertisements, national circulation magazine's articles, and the discourses conveyed by public power concerning the image and urban form of projects which stimulate the estate valuation in Maringá. Such images appear with specific intentions, using mainly the city's green areas as icons of propagation: parks, squares and large leafy streets, as a synonym of environmental quality.
A cidade verde, images and discourses: The case of Maringá (PR) Brazil
Keywords: Cidade Verde; Image; Maringá; Urban environment